Quantification of pesticide residues in some soils of Narshingdi area - Uddin, M Amin; Chowdhury, M Alamgir Z; Fardous, Z; Hasanuzzaman, M (Bangladesh Journal of Scientific Research, 2016)
Abstract not available Bangladesh J. Sci. Res. 29(1): 85-88, June-2016